Fibroblast Growth Factor 10 Reverses Cigarette Smoke- and Elastase-induced Emphysema and Pulmonary Hypertension in Mice - Hadzic, Stefan; Justus Liebig University Giessen (My University, 2022)
Chronic obstructive pulmonary disease (COPD) is a severe medical disorder characterised by chronic bronchitis and septal wall destruction (emphysema). Furthermore, COPD patients often suffer from at least mild pulmonary hypertension (PH) due to remodelling of the pulmonary vasculature. The main pathological driver is the inhalation of noxious particulate matter or gasses mainly coming from cigarette smoking but also from other sources such as air pollution. Several underlying mechanisms have been identified to drive disease development and progression. Such mechanisms involve protease/anti-protease disbalance, excessive nitrosative and oxidative stress and an augmented inflammatory response. Furthermore, recent studies support the idea that many developmental pathways are dysregulated in COPD, leading to impaired or even aberrant lung repair later in life. Despite the substantial efforts invested in the research and development of novel therapeutic approaches, COPD still remains an incurable and poorly treatable disease. In previous studies, fibroblast growth factor (FGF) 10 was suggested as a potential target involved in the reversion of cigarette smoke (CS)-induced emphysema and PH upon therapeutic inhibition of inducible nitric oxide synthase (iNOS) in mice. FGF10 is essential for lung morphogenesis, and it has been shown to control the survival and proliferation of alveolar epithelial progenitor cells during lung development. Moreover, it is suggested that impaired FGF10 signalling in patients is linked with higher susceptibility to develop COPD. However, a cause-effect relationship between FGF10 expression and COPD development, the underlying molecular mechanism, and interference with FGF10 signalling as possible therapy are not investigated yet. To address this issue, I analysed FGF-related signalling in human lung samples from healthy donors, smokers without and with COPD. Additionally, I performed hemodynamic and lung function measurements in Fgf10+/- and Fgfr2b+/- (FGF receptor 2b) mice after chronic exposure to CS and evaluated indicators of pulmonary vascular remodelling and emphysema histologically. In order to explore the potential of a therapeutic application, I overexpressed FGF10 in mice after elastase- or CS-induced lung injury. Furthermore, gene expression patterns during development and FGF10-mediated reversion of CS-induced emphysema and PH in mouse lungs were studied in dissected alveolar septa and pulmonary vasculature using microarray technology. I found decreased FGF10 expression in alveolar septa of the lungs explanted from smokers with and without COPD and in the lung homogenate of mice exposed to CS. I could pinpoint the decrease of FGF10 expression in interstitial lung fibroblasts isolated from COPD lungs. Such effects were also mimicked in healthy donor lung fibroblasts when in vitro exposed to CS extract or nitrosative/oxidative stress. Fgf10 and Fgfr2b haploinsufficient mice were more prone to develop CS-induced emphysema and PH. Moreover, animals with impaired FGF10 signalling developed spontaneous emphysema and PH and other typical pathomechanistic features that generally arise in response to CS exposure. These include 3-nitrotyrosine formation, increased matrix metalloproteinase (MMP) activity, apoptosis and various transcriptomic alterations. My data suggest that weakened β-catenin signalling and increased phosphorylation of Ak strain transforming (Akt) could underlay emphysema and PH development, respectively, in CS-exposed Wt mice and mice with impaired FGF10 signalling. Of interest, FGF10 overexpression could successfully reverse established elastase- and CS-induced lung injury in mice. Taken together, my data demonstrate that FGF10 signalling is crucial for adult lung homeostasis. Moreover, FGF10 signalling could be an integral part of the pathomechanism that leads to CS-induced emphysema and PH. Application of recombinant FGF10 or stimulation of the downstream signalling cascade thus might represent a novel therapeutic strategy for treating lung emphysema and PH in COPD.
Keywords: COPD; lung repair; FGF10; emphysema; pulmonary hypertension; ddc:500; ddc:570; ddc:610